PHYTOREMEDIATION OF TSS AND TDS FROM LANDFILL LEACHATE BY Equisetum hyemale - Ulfah, Maria; Kurniawati, Septiana; Nurwahyunani, Atip; Wijaya, Angelica Tricia (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2025)
Leachate contains TSS (Total Suspended Solid) and TDS (Total Dissolved Solid) which causes turbidity and a blackish brown color in the leachate. One effort that can be made to deal with environmental pollution caused by leachate is phytoremediation. This research aims to determine the effectiveness of water bamboo as a phytoremediation agent for TSS and TDS from landfill leachate. This research is an experimental study with a completely randomized design (CRD) with three treatment levels and three repetitions. The treatments given in this research were three variations of water bamboo, namely P0 : without water bamboo, P1: 750 g water bamboo, and P2: 1.000 g water bamboo. Based on research results, water bamboo is not effective in reducing TSS and TDS. The most optimal percentage reduction in TSS occurred in the P2 on the third day of the study (16.83%). The most optimal percentage reduction in TDS occurred in the P1 on the seventh day of the study (6.56%). The results of research show that phytoremediation can reduce Jatibarang Landfill leachate, especially TSS and TDS levels accumulated by the roots of water bamboo.